(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The purpose of nursing education is to train nursing staff that meets the needs of the population in terms of the number, professional qualifications and distribution of nursing staff. Therefore, the number of students, the number and composition of graduates of educational institutions of nursing should correspond to the needs and human resources of the healthcare sector.